2012
DOI: 10.1007/s00262-012-1376-4
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-C1/CT7 and MAGE-C2/CT10 are frequently expressed in multiple myeloma and can be explored in combined immunotherapy for this malignancy

Abstract: The exact function of MAGE-C1/CT7 and MAGE-C2/CT10 is not yet understood in multiple myeloma (MM). However, the homologs MAGE-C1/CT7 and MAGE-C2/CT10 genes encode highly immunogeneic cancer/testis antigens (CTAs) and can be potential targets for T cell-based immunotherapy. MAGE-C1/CT7 and MAGE-C2/CT10 mRNA expression were investigated in MM patients, solitary plasmacytomas, monoclonal gammopathies of undetermined significance (MGUS) and bone marrow (BM) aspirates from healthy donors by RT-PCR. MAGE-C1/CT7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
0
16
0
11
Order By: Relevance
“…MAGEC1 belongs to cancer/testis (CT) antigen family. The expression of MAGEC1 is frequently elevated in a variety of cancers [32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…MAGEC1 belongs to cancer/testis (CT) antigen family. The expression of MAGEC1 is frequently elevated in a variety of cancers [32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…Cancer-germline gene expression is induced through promoter demethylation by DNA demethylation agents (15,20,21). MAGE-A3 and MAGE-C2 (MAGE-A3/C2) have been recognized as attractive potential targets for cancer immunotherapy (2227). Previous studies have indicated that overexpression of MAGE-A3/C2 is associated with tumor metastasis and poor clinical outcome (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Its expression correlates strongly with plasma cell proliferation index, paraprotein levels, and reduced time to relapse, rendering CT7 a significant and independent negative prognostic factor for MM [3]. Evidence suggests that CT7 may play a gatekeeper function in terms of MAGE co-expression in MM [5]. CT7 may also play central roles in anti-apoptosis, in the dysregulation of cell cycle control and tumor progression, and in the development of chemotherapy resistance [3, 4, 6, 7].…”
Section: Introductionmentioning
confidence: 99%